"Tercera Edad" y prácticas alimentarias: entre la autonomía, las ayudas y el cuidado - Espeitx Bernat, Elena; Contreras Hernández, Jesús (ENDOXA, 2002)
The authors analyse reciprocal relations as a human resource for old people. They point out the multiplex contents of social relationships that enable and sustain distribution and allocation of resources and the changing forms of everyday interdependences.